Ion sensing organic electrochemical transistor - Ng, Derrick Zhan Hao (2019)
Some advantages of Organic Electro-Chemical Transistor (OECT) such as high transconductance, biocompatibility, and easy to fabricate, has led OECT into deeper research. OECT having a large transconductance makes them a good transducer by converting minute physical information into sensible electrical information. This project exploits on this concept and utilises the OECT for ion sensing. In the following chapters of this report will discuss the fabrication process of OECT, the testing of the devices and followed by the analysis of the test results. The fabrication of OECT will be separated into two parts as there are two different materials used, namely PEDOT:PSS and P3HT. PEDOT:PSS devices will be used mainly for ion sensing test while P3HT will be used for OECT channel optimization. From the testing for PEDOT:PSS devices, as the ion concentration of the electrolyte increases, the voltage where the transistor goes into saturation mode become lower. At the small window at which the transistor goes into saturation, the sensitivity of the device is very high as a small change in gate voltage or ion concentration will result in a large increment in drain voltage. As for the P3HT devices, the micropatterning technique was successful in changing the structure of the channel. However, the devices do not exhibit the characteristics of OECT probably due to the thickness of the polymer film.